EFFICACY OF PHENYLEPHRINE INFUSION VERSES COLLOID PRELOADING IN RESOLVING HYPOTENSION DUE TO SPINAL ANAESTHESIA DURING CAESAREAN SECTION - Shah, Azmat Ali; Rasool, Ahsan; Alam, Muhammad Adeel; Naseem, Yasir; Rasool, Maleeha; Hussian, Atif; Jadoon, Shandana; Shah, Ejaz Ali; Malik, Attique Afzal; Ahmed, Naveed; et al. (Journal of Ayub Medical College Abbottabad, 2018)
Background: Spinal anaesthesia causes hypotension that is countered through various methods. Phenylephrine is a vasoconstrictor and haemocoel increases the intravascular vascular volume; both have an effect in preventing this hypotension; but their comparison has not been done in local setting. Methods: Randomized control trial was conducted in month of June, 2017 at Ayub Teaching Hospital, Abbottabad. Block randomization with sealed envelopes was employed. Sample size was set at 90. Two equal groups were formed; Group A received 500 ml of haemocoel before spinal anaesthesia administration and Group B received 300µg of phenylephrine in 100ml infusion over 3 minutes. Results: An average drop of 8.2 mmHg, 9.7 mmHg and 3.1 mmHg in MAP was observed in Group A participants at 5 minutes, 10 minutes and 15 minutes respectively after spinal anaesthesia. In Group B, an average drop of 1.2mmHg was observed in first 5 minutes. MAP did not change significantly from this value throughout the monitoring period. There was a drop of 1.2 mmHg at 5 minutes in group B. After this, no further drop in blood pressure was observed. Conclusion: Phenylephrine infusion is better than haemocoel preload in preventing hypotension due to spinal anaesthesia. Keywords: phenylephrine infusion; spinal anaesthesia; Hypotension